Transnational organized crime and natural resources trafficking: funding conflict and stealing from the world's most vulnerable citizens - Liddick, Don (Lexington Books, 2020)
"Analyzes the transnational, illicit traffic in conflict commodities, including the smuggling of precious gems, wildlife products, oil, and other high-value goods and elucidates the structure and operation of transnational criminal networks, detailing how illicit profits finance war, terrorism, and human rights abuses"--